Edukasi Media Booklet Meningkatkan Pengetahuan Ibu Tentang Stunting: Penelitian Quasi Eksperimental - Damayanti, Dini; Linda (WOMB Midwifery Journal, 2024)
The growth and development of children during the toddler stage are the foundation for their success in the future. Stunting is one of the indicators of suboptimal growth. Lack of knowledge about stunting is one of the factors influencing its high occurrence. This quasi-experimental study aims to determine the improvement in maternal knowledge about stunting before and after receiving education through a booklet. The study was conducted on 30 respondents, who were given the same questionnaire before and after the intervention, with a 3-hour gap after receiving education using the booklet. Data analysis followed a paired T-test. Based on the research results, it is evident that the majority of respondents are aged 20-35 years, with most being high school graduates and not employed. And the results of the analysis showed that there was an increase in maternal knowledge about stunting before being given booklet media education with an average 76.83%  and after being given booklet media education with an average  81.83%, with a p-value of 0.000, indicating significance (p < 0.05). Therefore, it can be concluded that there is an impact of the media booklet education on maternal knowledge about stunting. Providing education through booklets to mothers with young children is beneficial in preventing stunting. Booklets are an effective health education medium as they enhance maternal knowledge about stunting and are practical to carry and read anytime.